Finland : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
In light of potential changes in fiscal policy in Finland, the impact of changes in the fiscal stance on short-term economic growth is an issue of interest. This paper estimates the short-term impact of fiscal policy on growth in Finland. The estimates are based on a structural vector autoregression (SVAR) model. However, identifying the long-term impact of changes in labor taxes on employment and growth is not an easy task. Although fiscal policy influences GDP in the short-term, the impact remains small compared with results.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet